Experimental facility control system for optical studies in the frame of problem solving of brain hematoma diagnostics; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Novoseltseva A. (Electronic engineering, 2015)
Title screen